PENINGKATAN HASIL BELAJAR DENGAN QUIZIZZ PAPER MODE DALAM PEMBELAJARAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) - Hersiyati Palayukan; Sitti Rahmi; Tatik Retno Murniasih; Indah Panglipur (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
The use of instructional media is expected to increase student motivation and interest in learning. One medium that can provide motivation and fun for students and teachers is the quizizz paper mode. The process of evaluation or assessment using quizizz paper mode media is a medium that is close to the development of information technology. The use of cellphones is directed towards media support for the rest, making the evaluation media with the quizizz paper mode very interesting. It is very interesting to study about improving learning outcomes with quizizz paper mode in learning with RME for students. With this type of qualitative research using pre-test and post-test instruments. The instrument was validated by experts with valid results. While the teacher observed the implementation of RME learning with the results that all steps could be carried out. The results of the research are that it can increase student learning outcomes to 86% of the remaining completion. So an increase of 50% of the results at the beginning of learning. The application of the quizizz paper mode can be continued by adding validation to the teacher's teaching documents.